Channel Coordination of Dual-Channel Supply Chain with C2M Manufacturer Introducing The Private Label - Yue, Siqi; Wang, Jinling; Liu, Bin (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
The thriving development of E-commerce platforms has injected new vitality into the C2M (Customer-to-Manufacturer) business model. However, it has also introduced a new challenger-the private label retailer. Given the escalating influence of private label retailers, the strategic introduction and coordination of the supply chain by C2M manufacturers have emerged as pivotal challenges. We analyze a C2M manufacturer's pricing strategies in three dual-channel supply chain models: centralization, decentralization, and partial centralization. In these models, the C2M manufacturer acts as a Stackelberg leader, while the private label retailer and platform act as followers. Analysis of both symmetric and asymmetric channel scenarios demonstrates that C2M manufacturers favor centralizing the supply chain. Consequently, we explore coordination strategies for Dual-channel supply chains and determine that the C2M manufacturer's contract, which incorporates wholesale and direct channel pricing, effectively coordinates the dual-channel supply, benefiting the retailer and platform but not the C2M manufacturer. We illustrate how such a contract, coupled with a complementary agreement like a two-part tariff or profit-sharing, can effectively coordinate the dual-channel supply chain, creating a win-win-win situation for the C2M manufacturer, private label retailer, and platform.